'Embowered in a mass of vegetation': Confinement and Predatory Plants in Fin-de-Siècle Fiction. (March 2023) - Melissa, Purdue
Abstract : In our present moment of ecological crises, stories about nature fighting back take on new significance. This article looks back at fin-de-siècle stories about predatory plants that entrap people, examining texts such as Edmond Nolcini's 'The Guardian of Mystery Island' (1896), H.G. Wells' 'The Flowering of the Strange Orchid' (1894), and Lucy H. Hooper's 'Carnivorine' (1889). These stories focus on killer plants that grab and confine characters with their tentacle-like branches and vines, ultimately suffocating them in their foliage. Like other gothic monsters, these plants reveal societal anxieties (colonialism, women, degeneration, and so on) at moments of transition. Given our twenty-first-century anxieties about environmental destruction, we need to look back at ecophobic moments in earlier literature to understand, as Simon C. Estok argues in 'Theorizing the EcoGothic', 'how monstrosity is central to an environmental imagination that locates the human as the center of all things good and safe' (34). Ideally, this historical interrogation can help us transition to new and healthier relationships with our environments in the present.